Collapse failure of layered composite pipe - Akmal Ariffin (2015)
This report presents the investigations on the critical collapse pressure of composite pipes through experimental and numerical analysis. Experimental analysis was carried out by conducting an External Pressure Collapse Test on the composite pipe. Various experimental setup and instrumentations were done to setup the test facility. Acoustic emission devices and strain gauges were used as measuring instruments to collect important data on the collapse of the composite pipe. Experimental data was analysed and the critical collapse pressure of the composite pipe was successfully obtained. Prior to experimental analysis, numerical analysis was done to predict the collapse pressure of the composite pipe. Numerical analysis was done through Finite Element Analysis using ABAQUS v6.14 modelling software. A simulation of the collapse test was carried out and the critical collapse pressure of the composite pipe was obtained. Simulation procedures are illustrated in the report. Values obtained from experimental analysis and numerical analysis were then compared and analysed. The main factor affecting the difference in the values is geometric imperfections of the composite pipe. Further recommendations were stated to improve future testing in order to better enhance the investigations done on the critical collapse pressure of composite pipes.